The Influence of Non-Physical Work Environment on Employee Performance with Work Discipline as a Mediating Variable (Study on Klaten Post Office Employees) - Risna Risna; Ismi Darmastuti (International Journal of Economics and Management Research, 2026)
This study aims to analyze the effect of the non-physical work environment on employee performance with work discipline as a mediating variable among employees of the KC Klaten Post Office. This study employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), processed with SmartPLS version 4 software. The population consists of 47 employees, and the sampling technique used is non-probability sampling with a saturated sampling method. The results of the study show that the non-physical work environment does not affect employee performance. The non-physical work environment has a positive and significant effect on work discipline, and work discipline has a positive and significant effect on employee performance. Furthermore, work discipline is proven to act as a mediating variable in the relationship between the non-physical work environment and employee performance.